2017
DOI: 10.1186/s12998-016-0133-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of thrust manipulation for non-surgical shoulder conditions

Abstract: PurposeAlthough many conservative management options are available for patients with non-surgical shoulder conditions, there is little evidence of their effectiveness. This review investigated one manual therapy approach, thrust manipulation, as a treatment option.MethodsA systematic search was conducted of the electronic databases from inception to March 2016: PubMed, PEDro, ICL, CINAHL, and AMED. Two independent reviewers conducted the screening process to determine article eligibility. Inclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 68 publications
2
29
1
Order By: Relevance
“…The existing research literature regarding effect of spinal manipulation and mobilization on cardiovascular parameters is still ambiguous. Studies corroborate 11 , 13 , 14 , 15 , 16 , 17 , 18 , 21 , 22 , 23 , 26 , 27 , 28 as well as contradict 12 , 19 , 20 , 24 , 25 the effects of manual therapy on cardiovascular parameters. These studies also have various methodological flaws.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The existing research literature regarding effect of spinal manipulation and mobilization on cardiovascular parameters is still ambiguous. Studies corroborate 11 , 13 , 14 , 15 , 16 , 17 , 18 , 21 , 22 , 23 , 26 , 27 , 28 as well as contradict 12 , 19 , 20 , 24 , 25 the effects of manual therapy on cardiovascular parameters. These studies also have various methodological flaws.…”
Section: Introductionsupporting
confidence: 57%
“…Most of the studies were done in USA (nine) 11 , 12 , 19 , 21 , 22 , 23 , 25 , 27 , 28 followed by Australia (two), 17 , 18 Spain (two), 13 , 24 Canada (two). 14 , 16 One study each was conducted in Brazil, 15 France 16 and Malaysia. 20 Only randomized control trials, either on healthy population or symptomatic population (such as subjects with spinal pain or hypertension), that compared the intervention to either a placebo or a control group were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was also reported in a systematic review in which thrust manipulation was investigated as a treatment option for nonsurgical shoulder conditions, verifying that there was a reduction in pain, although active and sham treatments were comparable. 33 Similar to this result, the study of Kardouni et al, 11 who evaluated patients with shoulder impingement syndrome after thoracic manipulation, found that both the manipulation group and the placebo group presented a reduction in pain. Two other studies obtained the same outcome as those of the present study for pain, verifying a decrease after manipulation in participants with shoulder impingement syndrome, both in the manipulation group and placebo group.…”
Section: Discussionsupporting
confidence: 56%
“…3 ). Once the painful movement is identified, the patient rates his/her pain on a numeric rating scale and then the physiotherapist attempts to modify it applying specific procedures [ 31 , 57 , 84 89 ] (see Table 3 ).
Fig.
…”
Section: Is It the Time To Move Towards An Integrated Clinical Framewmentioning
confidence: 99%